2003
DOI: 10.4049/jimmunol.171.1.360
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Role of ZAP-70 and Src Homology 2 Domain-Containing Leukocyte Protein of 76 kDa in the Prolonged Activation of Extracellular Signal-Regulated Protein Kinase by the Stromal Cell-Derived Factor-1α/CXCL12 Chemokine

Abstract: Stimulation of T lymphocytes with the ligand for the CXCR4 chemokine receptor stromal cell-derived factor-1α (SDF-1α/CXCL12), results in prolonged activation of the extracellular signal-regulated kinases (ERK) ERK1 and ERK2. Because SDF-1α is unique among several chemokines in its ability to stimulate prolonged ERK activation, this pathway is thought to mediate special functions of SDF-1α that are not shared with other chemokines. However, the molecular mechanisms of this response are poorly understood. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
73
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(75 citation statements)
references
References 48 publications
2
73
0
Order By: Relevance
“…SDF-1 can guide the movement of immune cells in vivo, and it can induce tight adhesion of rolling cells to activated endothelial cells, followed by their subsequent transendothelial migration. SDF-1 also enhances T cell responses to Ag stimulation via the secretion of cytokines and the promotion of cell survival (31,32). In the present study, we have found that an adaptor molecule, STAP-2, is a novel regulator of SDF-1␣-induced chemotaxis of T cells.…”
Section: Discussionmentioning
confidence: 53%
“…SDF-1 can guide the movement of immune cells in vivo, and it can induce tight adhesion of rolling cells to activated endothelial cells, followed by their subsequent transendothelial migration. SDF-1 also enhances T cell responses to Ag stimulation via the secretion of cytokines and the promotion of cell survival (31,32). In the present study, we have found that an adaptor molecule, STAP-2, is a novel regulator of SDF-1␣-induced chemotaxis of T cells.…”
Section: Discussionmentioning
confidence: 53%
“…In addition to signaling downstream of the TCR, SLP-76 has been implicated in chemokine signaling in the Jurkat model system [36]. In this study, SLP-76 was found to be phosphorylated downstream of stromal cell-derived factor (SDF)-1a and to be required for Ca 2+ flux and prolongation of ERK phosphorylation in response to SDF-1a stimulation.…”
Section: Introductionmentioning
confidence: 69%
“…In Jurkat T cells, SLP-76 is required for prolonged ERK phosphorylation and for Ca 2+ flux following SDF-1 stimulation [36]. However, the SLP-76/Gads interaction is dispensable for SDF-1-induced ERK phosphorylation [36].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…86,89 CXCR4 signaling also involves the Ras-activated signaling pathway, several src-related kinases such as Src, Lyn, Fyn and Lck, T-cell activating molecule ZAP-70 and vav. 90 Recent evidence from other [91][92][93] and our 70 laboratories indicates the role of small GTPases in CXCR4 signaling. Activation of these GTPases is crucial for cell migration to an SDF-1 gradient.…”
Section: Biological Effects Of the Sdf-1-cxcr4 Axismentioning
confidence: 99%